Olives and olive oil bioactive constituents - Boskou, Dimitrios; ScienceDirect eBooks (Urbana, Illinois : AOCS Press, 2015)
The market is flooded with products posing as elixirs, supplements, functional foods, and olive oil alternatives containing phenols obtained from multiple olive sources. This technically-oriented book will be of value to nutritionists and researchers in the biosciences. It unravels the body of science pertaining to olive minor constituents in relation to new chemical knowledge, technological innovations, and novel methods of recovery, parallel to toxicology, pharmacology, efficacy, doses, claims, and regulation. Topics include: the biological importance of bioactive compounds present in oli.
""General Factors That Influence the Final Concentration and Quality of Biophenols""""Quantitative Changes of the Concentrations of Specific Bioactive Components during Olive Oil Production""; ""Waste as a Raw Material for the Isolation of Bioactive Components""; ""Conclusion""; ""References""; ""Chapter 7. Research and Innovative Approaches to Obtain Virgin Olive Oils with a Higher Level of Bioactive Constituents""; ""Introduction""; ""Virgin Olive Oil Production: Technological Aspects and Minor Components""
Print version record.
Includes index.
Elsevier
Keywords: Plant bioactive compounds; Plant polyphenols; Olive oil -- Analysis; Olive oil -- Therapeutic use; Olive; NATURE -- Plants -- General; Olive; Olive oil -- Analysis; Olive oil -- Therapeutic use; Plant bioactive compounds; Plant polyphenols; Electronic books